2014
DOI: 10.1097/acm.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Electronic Health Record (Sim-EHR) Curriculum

Abstract: Electronic health records (EHRs) can improve many aspects of patient care, yet few formal EHR curricula exist to teach optimal use to students and other trainees. The Simulated EHR (Sim-EHR) curriculum was introduced in January 2011 at Oregon Health & Science University (OHSU) to provide learners with a safe hands-on environment in which to apply evidence-based guidelines while learning EHR skills. Using an EHR training platform identical to the OHSU EHR system, learners review and correct a simulated medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 6 publications
(6 reference statements)
0
38
0
Order By: Relevance
“…With reforms in medical education, there has been increasing emphasis on simulation training as it has been shown to increase knowledge and skills in invasive procedures as well as communication in a realistic environment (Wayne, Barsuk, O'Leary, Fudala, & McGaghie, 2008;Wayne, Didwania et al, 2008;Zendejas, Brydges, Wang, & Cook, 2013). Prior studies in EHR simulation have suggested EHR simulation promotes quality patient care as well as improvement in the identification of patient safety issues in critically ill patients (Landman et al, 2014;Milano, Hardman, Plesiu, Rdesinski, & Biagioli, 2014;Stephenson et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…With reforms in medical education, there has been increasing emphasis on simulation training as it has been shown to increase knowledge and skills in invasive procedures as well as communication in a realistic environment (Wayne, Barsuk, O'Leary, Fudala, & McGaghie, 2008;Wayne, Didwania et al, 2008;Zendejas, Brydges, Wang, & Cook, 2013). Prior studies in EHR simulation have suggested EHR simulation promotes quality patient care as well as improvement in the identification of patient safety issues in critically ill patients (Landman et al, 2014;Milano, Hardman, Plesiu, Rdesinski, & Biagioli, 2014;Stephenson et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…In 2009, Chertien and colleagues surveyed U.S. medical schools on incidence of unprofessional postings on social media by medical students. Sixty percent of the schools responded and of the respondents, 60% of the schools (Milano et al, 2014) reported unprofessional postings. This included violations of patient privacy, evidence of intoxication or substance abuse, profanity, discriminatory language and sexually suggestive content.…”
Section: Enhancing Communication Through Social Mediamentioning
confidence: 99%
“…Educational training programs struggle with efforts to incorporate use of operable EMRs in their curricula (Milano, Hardman, Plesiu, Rdesinski, & Biagioli, 2014;Wald, George, Reis, & Taylor, 2014). Student documentation in an actual patient EMR raises concerns related to patient safety, liability and accurate billing and reimbursement (Mintz, Narvarte, O'Brien, Papp, Thomas, & Durining, 2009).…”
Section: Filling the Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several others have called for hands-on EHR practice in medical education for documentation, specifically with an emphasis on balancing EHR documentation with patient engagement, practicing order entry in the EHR and utilizing decision aids that accompany EHRs (Atwater et al, 2016;Hammoud et al, 2012;Wald, George, Reis, & Taylor, 2014). Despite the transforming nature of the EHR in healthcare, its impact on patient care, and the numerous calls to adopt the EHR in medical education, EHRs have yet to be routinely integrated into medical curricula to teach optimal use to medical students (Kushniruk et al, 2012b;Milano, Hardman, Plesiu, Rdesinski, & Biagioli, 2014). More should be done to prepare individuals before they enter healthcare practice or the healthcare industry.…”
Section: Introductionmentioning
confidence: 99%